IMPLEMENTASI KOMPETENSI KEPRIBADIAN GURU DALAM PENGUATAN KARAKTER RELIGIUS PESERTA DIDIK MELALUI PEMBIASAAN DI KELAS IV MIN 2 SERANG - Lulu Rauhah; Istinganatul Nguluwiyah; Ikman Nur Rahman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Teachers have a crucial role in achieving educational goals, especially to strengthen the students’ religious character. In everyday life, a child often imitates what is done by people he usually meets because one of the characteristics of students at school age is imitating others. Therefore, a teacher with a good personality will more easily have a positive impact on strengthening the students’ religious character. This study aimed to determine teachers’ personality competence in strengthening the students’ religious character through habituation at grade IV MIN 2 Serang. The research method used in this research was descriptive qualitative. Data collection techniques used were interviews, observation, and documentation. This study indicated that the teacher of grade IV MIN 2 Serang had the personal abilities to reflect his personality. The teacher was able to implement personality competencies to strengthen the students’ religious character and provided good results in strengthening the students’ religious character.